Surgical treatment of the perineal hernia in dogs by internal obturator muscle elevating technic and reinforcement with swine auricular cartilage or polypropylene mesh - do Rego, Renato Otaviano; Henrique, Fernanda Vieira; Felipe, Gracineide da Costa; de Medeiro, Lylian Karlla Gomes; de Araujo, Sabrina Barros; Júnior, Antonio Gonçalves de Oliveira; Alves, Alane Pereira; Neto, João Moreira da Costa; Neto, Pedro Isidro da Nóbrega (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. do Rego R.O., Henrique F.V., Felipe G. da C., de Medeiros L.K.G., de Araújo S.B., de Oliveira Junior A.G., Alves A.P., Costa Neto J.M. & da Nó- brega Neto P.I. [Surgical treatment of the perineal hernia in dogs by internal obturator muscle elevating technic and reinforcement with swine auricular cartilage or polypropylene mesh.] Tratamento cirúrgico da hérnia perineal em cães pela técnica de elevação do músculo obturador interno e reforço com cartilagem auricular suína ou tela de polipropileno. Revista Brasileira de Medicina Veterinária, 38(Supl.1):99-107, 2016. Programa de Pós-graduação em Medicina Veterinária, Universidade Federal de Campina Grande, Avenida Universitária, s/n, Bairro Santa Cecília, Rodovia PB 110, Patos, PB 58700-970, Brasil. E-mail: renato_otaviano@yahoo.com.br The objective of this study was to evaluate the efficiency of the use of swine auricular cartilage preserved in glycerin to 98% compared to polypropylene mesh as a reinforcement in the surgical reconstruction of the pelvic diaphragm in the perineal hernia in dogs. 11 male dogs were used, of different breeds, aged between five and 15 years, weighing between 4.4 and 18.7 kg, which were randomly divided into two groups, CG and TG. One animal of the TG was undergone to bilateral hernia. The perineal hernia was corrected by internal obturator muscle elevating technic in both groups, and the animals of CG was tightened up the pelvic diaphragm with swine auricular cartilage graft preserved in 98% glycerin and in GT animals was used the polypropylene mesh as a reinforcement. In all animals orchiectomy was performed immediately the after herniorrhaphy. The animals were evaluated until the 90th day after surgery by clinical and ultrasonographic analysis of the perineal region. Results showed no statistical difference between the reinforcement with swine auricular cartilage and the polypropylene mesh. In the proposed evaluation period there were no hernia recurrences in GT, and only in one case in the GC, 90 days after surgery. It was observed the occurrence of other complications, such as contralateral side herniation in one animal of GT and other of GC and urinary incontinence in one animal of GC. There was a reduction in prostate size in all patients, starting 10 days after orchiectomy. It was concluded that the swine auricular cartilage implant is an alternative as viable as the polypropylene mesh to strengthen the repair of the pelvic diaphragm in dogs affected by perineal hernia.